Pengaruh Pembiayaan Musyarakah, Mudharabah, Murabahah, Risiko Pembiayaan, dan Risiko Operasional terhadap Profitabilitas pada Bank Umum Syariah (BUS) - Eka Nur Laily; Wiwik Fitria Ningsih; Mainatul Ilmi (Institut Teknologi dan Sains Mandala, 2022)
This study aims to examine the effect of musyarakah financing, mudharabah financing, murabahah financing, financing risk, and operational risk on profitability of Islamic Commercial Banks 2017-2021. The population of this study is Islamic Commercial Banks registered in the Otoritas Jasa Keuangan, using purposive sampling technique in selecting samples. The data used is secondary data obtained from the Financial Statements of Islamic Commercial Banks in Indonesia published 2017-2021. The data analysis method used is multiple linear regression analysis using IBM SPSS Statistic 22. The results of this study indicate that financing risk partially affects the profitability of Islamic Commercial Banks. Meanwhile, musyarakah financing, mudharabah financing, murabahah financing, and operational risk don’t have partial effect on the profitability of Islamic Commercial Banks. Simultaneously, musyarakah financing, mudharabah financing, murabahah financing, financing risk, and operational risk affect the profitability of Islamic Commercial Banks.